Barriers Associated With Palliative Care In Dementia: A Review Of The Literature - Elaine Araújo Aires dos Santos (Brazilian Society of Geriatrics and Gerontology, 2024)
INTRODUCTION: Dementia syndromes are a major cause of mortality and disability in the population. Although these patients bear a high burden of symptoms and comorbidities, the provision of palliative care is delayed until there are excessive symptoms or death is near. OBJECTIVE: To undertake an integrative review of the literature that addresses palliative care in the dementia syndromes, identifying limitations and barriers that preclude or hinder the introduction of palliative care for patients with dementia. METHOD: The MEDLINE (via PubMed), WEB OF KNOWLEDGE, and SCOPUS databases and the SCIELO Digital Library were searched to identify articles published in the last 10 years that addressed barriers to the introduction of palliative care in dementia. RESULTS: Six articles were identified, which discussed the following as main barriers: lack of knowledge, unpredictability of the disease, lack of criteria for indications, lack of communication, limited access and resources, beliefs and preconceptions in relation to death, and refusal by the patient and family. CONCLUSION: Additional investment is needed in education of professionals and the population on the indications and importance of palliative care, as well as in communication strategies as a way to facilitate the effective introduction of such care for people with dementia syndromes.